The animal figure in Astrid Lindgren’s work - David Rudd (Barnboken: Tidskrift för Barnlitteraturforskning, 2011)
At the age of 78 Lindgren began her campaign of writing to the newspapers, her correspondence subsequently being collected in a book called Min ko vill ha roligt (“My Cow Wants to Have Fun”) (1990) – the original letter being about a lovesick cow that goes in search of a bull, rather than suffer artificial insemination. This led Lindgren to look at other farming methods, and to the eventual passing in 1988 of the “Lex Lindgren”, for the more humane treatment of animals.